2019
DOI: 10.1002/ccd.28598
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous intraluminal downsizing of systemic‐to‐pulmonary artery shunts: a novel application of the Diabolo stent technique—Case series and description of the technique

Abstract: Objective This article aims to describe the feasibility of a novel application of the Diabolo stent technique for percutaneous downsizing of systemic‐to‐pulmonary artery shunts in patients with pulmonary overcirculation. Background Pulmonary overcirculation can lead to systemic hypoperfusion, impaired systemic oxygen delivery, and hemodynamic instability especially in patients with single‐ventricle physiology. Different medical and surgical strategies to treat pulmonary overcirculation have been reported so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Anticoagulant therapy could be considered in cases with thrombotic or in subjects at high risk for thrombotic events. Heparin was given before stenting for all patients with close monitoring of activated clotting time around 200 s ( 66 , 95 ). Post-procedure, continuous intravenous heparin infusion was given and was followed by oral aspirin ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulant therapy could be considered in cases with thrombotic or in subjects at high risk for thrombotic events. Heparin was given before stenting for all patients with close monitoring of activated clotting time around 200 s ( 66 , 95 ). Post-procedure, continuous intravenous heparin infusion was given and was followed by oral aspirin ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…This delay can go up to a median of 8.8 years as reported by Bonnet et al ( 31 ). Another study showed that shunts downgraded in size with endovascular stenting were all patent at a median follow-up of 7.3 months with no signs or symptoms of pulmonary over-circulation ( 95 ). Also, no procedure-related mortality was reported during follow-up period ( 71 , 90 , 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…While this technique has been reported in the management of systemic-to-pulmonary artery shunts (weight range 7.3-17 kg), this is the first case, to our knowledge of its use in an RV-PA conduit (weight 3 kg). 8 Disadvantages of this technique include the long delivery sheath, which can potentially lead to hemodynamic instability due to tricuspid regurgitation. In addition, iatrogenic heart block is a known risk during stent placement in Sano (RV-PA) conduits, though did not occur in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The configuration was comparable with that depicted in fig. 1 of Maschietto et al 8 A 7F × 48 cm Mullins Guiding Sheath (Cook Medical LLC) was advanced over a 0.035'' support wire into the right pulmonary artery. Before removing the dilator, the 0.035'' wire was exchanged for a 0.018'' support wire to accommodate the mounted stent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation